APB featured expertise: Associate Professor Ts. Dr. Janudin Sardi - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
Appointed as the Dean of the Akademi Pengajian Bahasa from 1st July 2022, Associate Professor Ts. Dr. Janudin Sardi is no stranger to putting on different hats when he steps into the office. He has worked in numerous portfolios that range from research to educational technology. Не previously served the Institute of Leadership and Quality Management (iLQAM) and closely worked with his ilQAM team members whom he views to be like a tight-knit family. As he possesses a strong educational background in the Arabic language and is passionate in the intricacies of the language, he was exhilarated to be selected as the representative of UITM to develop an e-Learning project for an Arabic course in 2002.